Neotype designation of Oribatula nativa Tseng, 1984 (Acari, Oribatida, Oribatulidae) - Ermilov, Sergey G.; Liao, Jhih-Rong (Zootaxa, 2018)
The type material of oribatid mites (Acari, Oribatida) of Tseng’s collections were lost, therefore, designation of neotypes is necessary to ensure stability in zoological nomenclature. The neotype and paraneotypes of Oribatula nativa Tseng, 1984 (Oribatida, Oribatulidae) are designated. This species is redescribed based on adult material collected from Taiwan.